Self-confidence as a mediator of the relationship between competitive anxiety intensity and interpretation - Mellalieu, S. D.; Neil, R.; Hanton, S. (Research Quarterly for Exercise and Sport, 2006)
The aim of this study was to examine whether self-confidence mediated the relationship between competitive anxiety intensity and direction. Elite (n = 102) and nonelite (n = 144) participants completed the self-confidence subscale of the Competitive Trait Anxiety Inventory-2 and the worry and somatic subscales from the Sport Anxiety Scale. Consistent with procedures recommended by Baron and Kenny (1986), linear regression analyses were used. The findings far elite athletes revealed worry intensity to significantly predict self-confidence and worry direction. However, when self-confidence was controlled, worry intensity did not predict worry direction over that which was significantly predicted by self-confidence. Within the analysis for somatic Symptoms, only self-confidence was found to predict somatic symptom direction. For the nonelite athletes, worry and somatic symptom intensity predicted both self-confidence and direction, and direction when self-confidence was controlled. The findings for the elite athletes suggest self-confidence mediates the relationship between performers' worry Symptoms and subsequent directional interpretations. However, the findings suggest that high levels of self-confidence and low symptom intensity are needed for nonelite athletes to demonstrate a less debilitative interpretation.